ASPECTS OF BIOLOGY OF ACEROPHAGUS PAPAYAE NOYES & SCHAUFF (HYMENOPTERA: ENCYRTIDAE), PARASITOID OF THE PAPAYA MEALYBUG - Wati, Mega; Rauf, Aunu; Pudjianto, Pudjianto (JURNAL HAMA DAN PENYAKIT TUMBUHAN TROPIKA, 2019)
Aspects of biology of Acerophagus papayae Noyes & Schauff (Hymenoptera: Encyrtidae), parasitoid of papaya mealybug. Acerophagus papayae Noyes & Schauff (Hymenoptera: Encyrtidae) is an important parasitoid of the papaya mealybug, Paracoccus marginatus Williams & Granara de Willink (Hemiptera: Pseudococcidae). The study was conducted with the objective to determine various aspects of the biology of A. papayae which include the effect of diet on adult longevity, fecundity and progeny, host stage susceptibility and preference, the effect of host stages on immature development, body size, and sex ratio of progenies.  Effects of diet on adult longevity was done in the absence of hosts. Fecundity was measured by the number of mealybugs parasitized. Host stage susceptibility and preference were carried out by exposing 2nd  and 3rd  nymphal instars and pre-reproductive adults of mealybugs to parasitoids. Results showed adult parasitoids fed with 10% honey solution lived almost fourfold longer than those provided only water. A. papayae parasitized 30.1±4.92 mealybugs, with a range of 13-60 mealybugs, during 5.8 days of adult life.  In no-choice (susceptibility) and paired-choice (preference) tests, the percentage of parasitized hosts were significantly greater in 2nd and 3rd instar nymphs than in adults. The mean immature developmental time of A. papayae was longer when the parasitoids develop in large host. Developmental time of male parasitoids was shorter than the females. Female wasps which emerged from hosts parasitized at the 3rd instar nymphs and adults were significantly larger than those from the 2nd instar nymphs.  Sex ratios of the offspring emerged from hosts that were parasitized as 2nd instars were strongly male-biased, while the later stages yielded more females than males.